Analysis Of The Influence Of Liquidity, Leverage, And Profitability On Stock Returns Of Manufacturing Companies In The Basic And Chemical Industry Sector Listed On The Indonesia Stock Exchange - Ananda, Geby Citra; Lubis , Zuhrianda Qois (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the effect of liquidity, leverage, and profitability on stock returns of manufacturing companies in the basic and chemical industry sector listed on the Indonesia Stock Exchange. The research is motivated by the importance of fundamental financial indicators as a basis for investors in assessing the potential returns of their investments. The study uses secondary data obtained from annual financial reports for the period 2020–2024 and employs panel data analysis techniques. A total of 18 companies were selected as samples using a purposive sampling method. Model testing was conducted using the Chow Test, Hausman Test, and Lagrange Multiplier Test, which ultimately indicated that the Fixed Effect Model (FEM) is the most appropriate model for the analysis. The results show that liquidity has no significant effect on stock returns. In contrast, leverage has a significant negative effect on stock returns, while profitability has a significant positive effect on stock returns. The adjusted coefficient of determination (Adjusted R²) of 0.551 indicates that 55.1% of the variation in stock returns can be explained by the three independent variables in the model. These findings emphasize that capital structure and the company’s ability to generate profits are crucial factors influencing investors’ expected returns, whereas short-term liquidity ability is not a primary consideration in determining stock return performance.